Endoscopic Pilonidal Sinus Treatment: A Tertiary Care Academic Center Experience - Gallo, Gaetano; Carpino, Antonio; De Paola, Gilda; Fulginiti, Serena; Novelli, Eugenio; Ferrari, Francesco; Sammarco, Giuseppe (Frontiers in Surgery, 2021)
Background Pilonidal disease (PD) represents one of the most common proctological diseases in young adults. Although several approaches to treating PD have been described, there is still a lack of agreement on which is the best. The aim of this study was to evaluate the long-term efficacy of endoscopic pilonidal sinus treatment (EPSiT) at a tertiary care academic center. Methods Between June 2017 and January 2021, a total of 32 patients (12 women (37.5%) and 20 men (62.5%)) with a mean age of 29.22 ± 12.98 years were treated with EPSiT. Pre- and post-operative symptoms were assessed with a score of 0–5. Success was defined as the absence of any subjective symptoms, as well as by complete post-operative wound healing. Results Most of the patients had a midline external opening (17/32; 53.1%), with a mean number of external openings of 2.41 (1–4) ± 1.04. The median post-operative pain score was 0, and the mean follow-up period was 22 (4–42) ± 11.49 months. The time to wound healing was reduced in patients with one opening (28.14 ± 4.06 days) compared to patients with two or more openings (33.64 ± 7.3 days) (p = 0.067). The mean operative time was longer in patients who subsequently had a recurrence (41.75 ± 6.24 vs. 34.18 ± 6.24 min; p = 0.031). The overall success rate was 87.5% (28/32), and the mean time to recurrence was 3.25 (2–5) ± 1.26 months. Conclusions EPSiT represents a viable option for the treatment of PD. More evidence and a longer follow-up period are needed to validate the results.